Pengaruh Ekstrak Tembuluk Kelapa Merah (Cocos nucifera var. rubescens) Terhadap Penurunan Kadar Glukosa Darah Pada Mencit (Mus musculus) - Novi, Winda Cinthia; Sutrisnawati, Sutrisnawati; Ramadhan, Achmad; Trianto, Manap; Masrianih, Masrianih; Kundera, I Negah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of red coconut embryo extract (Cocos nucifera var. rubescens) on reducing blood glucose levels in mice (Mus musculus). The research employed a true experimental method using a completely randomized design (CRD). A total of 24 mice were used, divided into 6 groups with 5 replications each. The normal control group (KN) was given food and water ad libitum, while the positive control (K+), negative control (Kâˆ’), and treatment groups (PI, PII, PIII) were induced with alloxan for 7 days. The positive control group (K+) was administered 1.3 mg of synthetic metformin per 20 grams of body weight. Both the normal control (KN) and negative control (Kâˆ’) groups were given food and water ad libitum. The treatment groups PI, PII, and PIII were administered red coconut embryo extract at varying concentrations. Treatment group 1 (PI) received 40% extract, group 2 (PII) received 60%, and group 3 (PIII) received 80%. Observation data were analyzed using ANOVA. The results showed that the red coconut embryo extract had a significant effect on reducing blood glucose levels in alloxan-induced mice. The most effective concentration was 40% (PI), with an average blood glucose level of 98.6 mg/dL.